Marine Ecolexicon of Noun-Verb of the Coast Community in Pesisir Barus, Central Tapanuli - Rosliana Lubis; Dwi Widayati (JURNAL ARBITRER, 2021)
This study aims to describe the lingual form, which is a manifestation of the understanding of the speech community of the environment towards its environmental dimension. The theory used in this research is ecolinguistic. Data in the form of basic lexicons and affixed lexicons related to the marine environment were collected through interviews with informants. Furthermore, the data were analyzed by grouping them based on the word class, environmental category, and the affixation process contained in the affixed words. The results of the study show that many marine environmental lexicons which are divided into noun lexicon and verb lexicon. The noun lexicon is divided into four lexicon categories, namely: (1) Marine Environmental Fauna Lexicon (88 lexicons); (2) Flora of the Marine Environment Flora (9 lexicons); (3) Lexicon of Facilities / Infrastructure for Marine Environmental Activities (16 lexicons); and (4) Nominal Environmental Lexicon (7 lexicons). The number of vocabulary that is still recorded in the cognition of the Barus coastal Malay language community indicates that the community is very familiar with its environment and therefore the vocabularies are preserved.